2018
DOI: 10.1210/js.2018-00130
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Benign and Synonymous Variants in CYP11A1 Cause Primary Adrenal Insufficiency Through Missplicing

Abstract: Primary adrenal insufficiency (PAI) is a potentially life-threatening condition that can present with nonspecific features and can be difficult to diagnose. We undertook next generation sequencing in a cohort of children and young adults with PAI of unknown etiology from around the world and identified a heterozygous missense variant (rs6161, c.940G>A, p.Glu314Lys) in CYP11A1 in 19 individuals from 13 different families (allele frequency within undiagnosed PAI in our cohort, 0.102 vs 0.0026 in the Genome Aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
2
30
0
3
Order By: Relevance
“…Consistent with previous reports, pubertal development (although delayed in the two older brothers) was normal in the sibship, with normal testicular volumes and Leydig cell function (19,24,25,26).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous reports, pubertal development (although delayed in the two older brothers) was normal in the sibship, with normal testicular volumes and Leydig cell function (19,24,25,26).…”
Section: Discussionsupporting
confidence: 91%
“…The partial nature of P450scc deficiency in this family is consistent with most of the published cases with similar genetic findings (19,24,25,26).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…64 Although the c.940G>A variant is predicted to cause a benign protein change (p.E314K), detailed molecular studies have shown that it generates a novel splice site so that missplicing occurs. 64,65 This variant is carried by approximately 1:140 people of European descent, but is likely to cause adrenal insufficiency only when inherited with a very rare disruptive change on the other allele. Partial CYP11A1 insufficiency can also occur in other populations, such as due to the p.R451W variant common in central Turkey.…”
Section: Nonclassic Cyp11a1 Deficiencymentioning
confidence: 99%